PEMBERDAYAAN PEREMPUAN NELAYAN PULAU MAITARA MELALUI PENGOLAHAN IKAN LAUT MENJADI BAKSO IKAN, NUGGET IKAN DAN STICK IKAN - Juharni Juharni; Muhammad Irfan; Fatma Muchdar; Rovina Andriani; Ikbal Marus (Universitas Mataram, 2023)
Maitara Island is one of the areas in the City of Tidore Islands, most of the people work as fishermen. The involvement of women in productive economic activities to manage coastal resources has not been recorded, many of which carry out marine resource management activities, are still limited to making crackers from fish, shredded fish, salted fish and others. This is a glimpse of the role of women's participation. The low level of education and lack of coaching can be used as reasons for the lack of women's participation in productive businesses. This PKM activity is to increase the knowledge and skills of the community, especially fisherwomen in making various processed fishery products and to assist women's involvement in the implementation of development programs. Implementation of training activities and assistance in the manufacture of various processed fishery products to be sold to help the family economy. Training and mentoring, namely socialization of the program to partners, provision of theory, preparation of training tools and materials for making fish balls, fish nuggets and fish sticks. The main ingredients for meatballs, nuggets and fish sticks are white fish meat. Types of fish that have white flesh. The tastier the fish meat used, the tastier the resulting meatball flavor will be. To get meatballs that are delicious and have a good texture, tapioca flour needs to be added 10% - 15% of the weight of the meat used. While sticks are snacks in the form of pastries made from fish and other ingredients as well as nuggets. Increased skills to make processed fishery products in special community service activities made from fish-based ingredients. Fishery product processing training activities are easily understood and raw materials are sufficiently available throughout the year, easy and inexpensive.